The Relative Frequency Of Small Vessel Cerebrovascular Disease And Brain Atrophy In MRI Of Patients With Psoriasis - Dadkhahfar, Sahar; Gheisari, Mozhdeh; Mahboubi-Fooladi, Zahra; Shahidi Dadras, Mohahmmad (Dermatology Practical & Conceptual, 2023)
Introduction: Psoriasis is a systemic autoimmune disease that is associated with numerous comorbidities.Objective: This study aimed to compare the prevalence of small vessel cerebrovascular disease (SVCD) and atrophic brain changes in MRI of patients with psoriasis and normal subjects.Materials and Methods: This case-control study was performed on 27 patients with psoriasis and 27 normal individuals who were referred to Shohada-e-Tajrish Hospital, Tehran, Iran during 2019 and 2020. Basic demographic and clinical information of participants were recorded. Brain MRI was performed for all individuals to examine the medial temporal atrophy (MTA) score, global cortical atrophy (GCA) score, and Fazekas scale. Finally, the relative frequencies of each parameter between the two groups were compared.Results: There was no significant difference in the frequency of the Fazekas scale, GCA, and MTA scores between the two groups. However, a mild trend was found for higher frequency of Fazekas scale, GCA, and MTA scores in controls in comparison with the case group. While there was no significant relationship between the Fazekas scale and disease duration (p=0.16), a significant and positive correlation was found between disease duration and GCA and MTA scores (p<0.001). There was no significant relationship between Fazekas, GCA and MTA status and other parameters.Conclusion: The increase in disease duration was significantly associated with increase in the incidence of cerebral atrophy, which may suggest the need for screening in terms of CNS involvement in psoriasis patients.